Strategi Pondok Pesantren dalam Penguatan Pendidikan Islam Moderat di Desa Lorejo Kecamatan Bakung - Muhammad Shalehuddin; Muhammad Arif Syihabuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
slamic education plays a crucial role in instilling religious and moral values amidst the challenges of globalization and the industrial era 4.0. Islamic boarding schools (pondok pesantren), as traditional Islamic educational institutions, hold a strategic position in shaping students' character through a moderate Islamic approach that emphasizes tolerance, inclusiveness, and rejection of radicalism. This study aims to examine the strategies implemented by Islamic boarding schools in strengthening moderate Islamic education in Lorejo Village, Bakung Subdistrict. The focus includes planning, implementation, and evaluation of these strategies. The findings indicate that the boarding schools positively influence the community’s religious behavior and foster an educational environment that promotes wasathiyah (moderate) values. However, challenges such as limited resources and conservative local culture must be addressed through adaptive and collaborative strategies